me Makna Cinta Abadi Pada Drama “Koi Wa Tsudzuku Yo Doko Made Mo” Dalam Teori Erich Fromm: Analisis Makna Cinta Dalam Drama Koi Wa Tsudzuku Yo Doko Made Mo - Mayang Rosalinda Gultom; I Wayan Wahyu Cipta Widiastika (Jurnal Daruma : Linguistik, Sastra dan Budaya Jepang, 2024)
The drama "Koi Wa Tsudzuku Yo Doko Made Mo” is an intriguing literary work that captivates the audience with its central theme of eternal love. This article aims to explore the meaning and interpretation of the concept of eternal love depicted in the drama using Erich Fromm's theory of love. Erich Fromm's theory provides a profound psychological perspective on love, emphasizing active involvement, affection, attention, responsibility, and respect in relationships. Through the qualitative descriptive method, this article will delve into the drama "Koi Wa Tsudzuku Yo Doko Made Mo" in more detail, capturing scenes, dialogues, and character behaviors that highlight the theme of eternal love. The findings of this research contribute significantly to appreciating the drama "Koi Wa Tsudzuku Yo Doko Made Mo" and the theme of eternal love integrated with Erich Fromm's theory of love. This article offers a comprehensive psychological understanding of how the concept of eternal love aligns with human experience and how it shapes the characters' relationships throughout the storyline.